Pengembangan Sumber Daya Manusia (SDM) terhadap Tingkat Etos Kerja Karyawan pada Hotel Santika Sukabumi - Hendita Yosepa; Acep Samsudin; Asep Muhamad Ramdan (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
Banking health is very important to be maintained because banks play an important role in society, especially as increasing the country's economic growth. This study aims to examine the effect of risk-based bank rating on financial distress. The risk-based bank rating ratio consists of risk profiles proxied by NPL and LDR, good corporate governance proxied by the size of the board directors and independent commissioners, earnings proxied by ROA, ROE, BOPO, and NIM, and capital proxied by CAR. The yardstick used in this research is the bankometer model. The research year is 6 years from 2013-2018. The population was all non-foreign exchange banks, amounting to 30. The sample was determined using purposive sampling, find 20 non-foreign exchange with data analysis techniques using logistic regression. Research data using SPSS 25. The results of the study found the influence of LDR, size of the board directors, NIM, and CAR. LDR ratio has a significant negative effect, board size has a significant positive effect, NIM has a significant negative effect, and CAR has a significant negative effect on financial distress. This because the fourth variable had an important thing on liquidity, independent oversight, interest income, and capital adequacy. Whereas NPL, independent commissioners, ROA, ROE, and BOPO do not affect financial distress. This because the value of each variable already appropriate with Bank Indonesia determination and it summed up that Non-Foreign Exchange Bank already apply it well. This shows that risk-based bank ratings can be a parameter of bank health.